Analisis Komunikasi Virtual Dalam Dunia Roleplayer Grup RP Palembang Platform Telegram - Alfiyah Humairoh; Suryati Suryati; Sumaina Duku (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
With the title "Analysis of Virtual Communication on the Palembang World RP Group Roleplayer Telegram Platform". This study describes how virtual communication in roleplayer games among teenagers, especially teenagers in the city of Palembang. This study aims to find out how the process of roleplayer users form virtual communication and analyze virtual communication in the telegram platform roleplayer world towards members of the RP Palembang group. The theory used in this research is social science theory and new media theory. The research method used in this study is a qualitative research method. The approach used by researchers in this study is through observation obtained by conducting observations and structured interviews to become a reference for researchers to understand in depth about virtual communication in telegram platform roleplayer games. From the research results that have been obtained from the observation and documentation of researchers, the author can explain the process of forming virtual communication between roleplayer players, the types of virtual communication that occur in roleplayer games, supporting factors and inhibiting factors for virtual communication for roleplayer players and the advantages of the telegram platform in forming virtual communication in the roleplayer world of RP Group Palembang members.